The Theory and Practice of Creative Coaching : Analysis and Methods. - Turner, Arthur (Anthem Press, 2023)
The Theory and Practice of Creative Coaching is the result of ten years of research and experimentation into the place and role of creativity in learning about and undertaking the skills of coaching in the workplace. The contents outline a wide variety of approaches and ideas to enhance and develop effective coaching relationship.